The Zulu girl and other poems - Ngidi, Sandile Brian (Rhodes University, Faculty of Humanities, School of Languages, 2019)
My thesis is a collection of English poems that converse with Mazisi Kunene's literary corpus. I draw from both Kunene's early works, which followed the pioneering work of the Zulu poet BW Vilakazi, and his socio" political later work, which is at once Pan African in scope and intent yet deeply rooted in a Zulu socio" linguistic milieu. Like Kunene, I aim to create a poetics of exile by working between languages, writing in Zulu and then translating into English to express my alienation in South Africa and what it means to be exiled from language and culture and speak a foreign language with your mother tongue. Here, I also take influence from the rich, evocative imagery in Palestinian poet Mahmoud Darwish's poetry of exile and the quest for a lost homeland, as well as Brazilian poet Adela Prado's wit and direct speech. I also engage popular contemporary forms of expression and use poetry to question some themes in the popular music genre maskandi, especially its rhetoric on identity, class and gender politics.
Keywords: Xhosa poetry